Leading an Academic Medical Practice (Springer International Publishing, 2018)
This book informs and supports medical educators and clinic leaders regarding the key clinical and administrative components necessary to run an academic medical practice. From a group of expert faculty from the Society of General Internal Medicine (SGIM) with years of experience in managing academic medical practices, this manual offers comprehensive guidance to the clinic director regarding critical factors involved with running an academic medical practice including, but not limited to: compliance with Accreditation Council for Graduate Medical Education (ACGME) requirements, clinic orientation and curricula implementation, clinic workflow challenges, billing, coding, and the Primary Care Exception Rule, productivity metrics and quality indicators, evaluation and feedback for trainees, faculty, and clinic staff, implementation of a Patient Centered Medical Home (PCMH), development of controlled substance prescribing policies, medical student involvement in resident clinics, and Veteran Affairs practices and non-traditional care settings. The scope of this book is sufficiently broad to be comprehensive and practical while still anticipating the further evolution of the academic medical practice in the years to come. Each chapter focuses on a particular aspect of clinic leadership and will offer real-world examples and management "pearls" for the clinic director. Chapters highlight common challenges and solutions and should be useful across disparate practice settings. This is an ideal resource for clinic directors, core faculty, and clinic leadership in academic outpatient medical practices, particularly those within the field of Internal Medicine, Primary Care, and related specialties. .